Giant intrapericardial lipoma: clinical and forensic implications - Bogdanović, Milenko; Pavlekić, Snežana; Milošević, Maja; Radnić, Bojana; Lakčević, Jovana; Veljković, Stefan; Alempijević, Djordje; Babić, Miloš D. (Vojnosanitetski pregled, 2023)
Introduction. Even though lipomas are the most common benign tumors, they are rarely found in the pericardial cavity. Although histopathologically benign, they can cause life-threatening complications by rapid growth and may therefore be clinically considered malignant. Case report. We present an 80-year-old female who was injured during a syncopal episode when falling from a standing height and suffered bodily injuries for which she was hospitalized. In the further course of her short-term hospital treatment, death occurred, and the cause of death was marked as “unknown”. At the autopsy, a dilated and tense pericardium filling up a large part of the chest cavity was noted. A well-encapsulated soft tissue mass, 20 × 18 × 3 cm in size, weighing 820 g, was visualized in the pericardial cavity. Histopathological examination revealed that the mass was a lipoma and showed acute myocardial necrosis; therefore, it was assumed that the cause of death was probably due to the compression of lipoma on coronary arteries. Conclusion. Even though intrapericardial lipomas are benign tumors, they can cause life-threatening complications and sudden cardiac death. There are numerous diagnostic methods capable of detecting intrapericardial lipomas, and with timely treatment, the patient can be cured.
Keywords: autopsy; cause of death; diagnosis; lipoma; myocardial infarction; pericardium; syncope